중학생의 부모애착이 교우관계에 미치는 영향: 학업 효능감의 매개효과를 중심으로 - 김정화; Jeong Hwa Kim (청소년복지연구, 2015)
본 연구의 목적은 중학생의 정서적 안정감과 행복감의 근간이 될 수 있는 교우관계의 중요성을 인식하고 중학생의 학교생활과 대인관계의 기초가 될 수 있는 교우관계에 대해 부모와의 애착관계를 통해 알아보고, 중학생의 학업수행에 중요한 역할을 하는 학업 효능감을 매개로 하여 부모애착이 중학생의 교우관계에 어떠한 영향을 미치는지를 알아보는 것이다. 연구대상은 대구지역을 중심으로 중학교에 재학 중인 215명을 조사하여 분석하였다. 분석을 위해 pearson 상관분석, 단순회귀분석, 다중회귀분석을 하였고 연구결과, 중학생이 지각한 부모애착 및 학업 효능감은 중학생의 교우관계에 직접적으로 영향을 미치는 것으로 나타났다. 그리고 중학생의 학업효능감은 부모애착과 중학생의 교우관계에서 부분매개 효과가 있는 것으로 검증되었다. 이러한 결과를 토대로 중학생의 교우관계 향상을 위하여 부모와의 애착을 강화시키고 학업 효능감의 중요성을 제시하였고, 학업 효능감을 매개로 하는 부모와의 애착과 교우관계에 대한 통합적 접근의 중요성을 강조하였다. The purpose of this study was to examine the influence of attachment to parent by Middle school students on their peer relationship and to whether academic self-efficacy mediated in the relationship between attachment to parent and academic self-efficacy. To obtain this purpose, subject was 215 middle-school students from Daegu area. The data collected was analyzed with pearson correlation analysis, regression analysis using IBM SPSS Statistics. The major findings in this are the following; First, attachment to parent was found to have on their peer relationship. Second academic self-efficacy was found to have on their peer relationship. Finally, attachment to parent was to have partial mediating effects in the relationship between attachment to parent and academic self-efficacy. Based on the results, the specific ways to improve attachment to parent and academic self-efficacy were suggested. importance of integrated approach between attachment to parent mediated academic self-efficacy with peer relationship was focused.